Teacher Differentiation Strategy In Islamic Religious Education Learning For Hyperactive Students At SDN Sumedangan 2 Pademawu Pamekasan - Wardatun Nisa; Zainol Hasan (Universitas Muhammadiyah Enrekang, 2026)
This study aims to describe the differentiation strategy of teachers in the learning of Islamic Religious Education to hyperactive students at SDN Sumedangan 2 Pademawu Pamekasan and to find out the obstacles and solutions in its implementation. This study uses a qualitative approach with a descriptive type of research. Data were obtained through observation, interviews, and documentation with informants, principals, Islamic Religious Education teachers, inclusion assistant teachers, and hyperactive students. Data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that teachers adjust learning through the differentiation of content, processes, and products according to the needs of hyperactive students. The delivery of material is carried out concretely and is associated with the daily life of students. Teachers also use hands-on practice, songs, individual approaches, and repetition of material so that students can understand learning more easily. Learning assessments not only focus on final grades, but also pay attention to the development of students' abilities during the learning process. The obstacles faced by teachers are students who find it difficult to focus, need more attention, and classroom management that is not fully conducive. To overcome this, teachers apply a patient approach, give personal attention, and instill an empathetic attitude to other students so that learning continues to run well.